2018
DOI: 10.1186/s12893-018-0367-6
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Abdominal Wall Desmoid type Fibromatosis: treatment paradigm after thirty two years

Abstract: BackgroundDesmoid-type fibromatosis is a benign mesenchymal neoplastic process. It exhibits an uncertain growth pattern and high recurrence rate. Previously radical surgical resection was the mainstay of treatment, but recently more surgeons are opting for conservative management with observation (“wait and see” policy). The authors intend to evaluate different therapeutic modalities and oncological outcomes for abdominal wall desmoid tumors.MethodsWe performed a retrospective study of patients who underwent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…5 Gronchi et al reported that the recurrence rate is unaffected by whether the margin is positive or negative. 6 Other studies 7 have reported that tumor size, age, and occurrence location are predictors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…5 Gronchi et al reported that the recurrence rate is unaffected by whether the margin is positive or negative. 6 Other studies 7 have reported that tumor size, age, and occurrence location are predictors.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, conservative approaches such as pharmacological or simple observation have been selected as treatment. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease occurs more frequently in female patients during their reproduction period, especially during pregnancy or in women with previous C-section [23]. Couto Netto et al present a study of 32 patients diagnosed with DT; 90% of them were female, 62.5% with previous pregnancies and 19% with surgical of the abdominal wall [25]. Leon et al (2015) present the case of a 24-year-old woman, pregnant in the 14 th week of gestation, presenting a palpable abdominal mass at the clinical examination.…”
Section:  Desmoid Tumorsmentioning
confidence: 99%
“…Previous studies have demonstrated that the long-term prognosis of patients with abdominal wall DTs is significantly better than that of patients with intra-abdominal DT. [ 4 , 5 ] Wilkinson et al [ 4 ] reported the prognosis of 50 patients with abdominal wall DTs who underwent surgical resection. Within a median follow-up period of 5 years, the local recurrence rate was only 8% (4/50).…”
mentioning
confidence: 99%